Association between systemic immune-inflammation index and cataract among outpatient US adults - Huang, Jin; Wu, Hongjiang; Yu, Fang; Wu, Fangkun; Hang, Chen; Zhang, Xiaoya; Hao, Yiting; Fu, Hao; Xu, Hongting; Li, Rong; Chen, Ding (Frontiers in Medicine, 2024)
Background While several studies have noted a higher SII correlates with multiple diseases, research on the association between SII and cataract remains limited. Our cross-sectional study seeks to examine the association between SII and cataract among outpatient US adults. Methods This compensatory cross-sectional study utilized NHANES data from 1999 to 2008 cycles, conducting sample-weighted multivariate logistic regression and stratified analysis of subgroups. Results Among 11,205 adults included in this study (5,571 [46.2%] male; 5,634 [53.8%] female), 2,131 (15.2%) had cataract and 9,074 (84.8%) did not have cataract. A fully adjusted model showed that SII higher than 500 × 109/L was positively correlated with an increased risk of cataracts among women (OR, 1.27; 95% CI, 1.02–1.59) (p = 0.036). However, no difference was found in the men subgroup, and there was no significant interaction between SII and sex. Conclusion Our results indicated that a SII higher than 500 × 109/L was positively correlated with an increased risk of cataracts in women. This study is the first to specifically investigate the impact of a high SII on cataract risk in outpatient adults in the United States. By effectively addressing inflammation, it is possible to mitigate cataract progression and significantly enhance patient outcomes.